Parameter optimization of sputtered Ti interlayer using Taguchi method - Bushroa, Abdul Razak; Masjuki, Haji Hassan; Muhamad, M.R. (University of Malaya, 2011)
The aim of this study was to optimize the process of coating a thin Ti film using a PVD magnetron sputtering system. The Ti thin film acted as an interlayer sandwiched between a substrate and a hard TiSiN coating. The substrates used were glass and high speed steel (HSS). An optimization of the process input parameters was carried out by utilizing Taguchi method. Morphological studies on the resultant coating were done using a field emission scanning electron microscopy (SEM). X-ray diffraction was utilized to analyze the crystal structure of the thin film. Micro scratch test was used to determine the adhesion strength of the coating/substrate system. Thin film Ti interlayers were successfully deposited on the substrates. The subsequent deposited TiSiN coatings on the substrates were very dense and uniform. The optimized input parameters of the Ti interlayer deposition resulted in an improved adhesion strength of the TiSiN coating on the substrate by 28.5%.